Extent of Surgery and Implications of Transection Margin Status after Resection of IPMNs - Marina Paini; Stefano Crippa; Filippo Scopelliti; Andrea Baldoni; Alberto Manzoni; Giulio Belfiori; Stefano Partelli; Massimo Falconi (Gastroenterology Research and Practice)
Appropriate surgical strategies for management of intraductal papillary mucinous neoplasms (IPMNs) of the pancreas are a matter of debate. Preoperative and intraoperative evaluation of malignant potential of IPMN and of patient’s comorbidities is of paramount importance to balance potential complications of surgery with tumors’ risk of being or becoming malignant; the decision about the extent of pancreatic resection and the eventual total pancreatectomy needs to be determined on individual basis. The analysis of frozen-section margin of pancreas during operation is mandatory. The goal should be the complete resection of IPMN reaching negative margin, although there is still no agreed definition of “negative margin.” Of note, the presence of deepithelization is often wrongly interpreted as absence of neoplasia. Management of resection margin status and stratification of surveillance of the remnant pancreas, based on characteristics of primary tumour, are of crucial importance in the management of IPMNs in order to decrease the risk of tumor recurrence after resection. Although risk of local and distant recurrence for invasive IPMNs is increased even in case of total pancreatectomy, also local recurrence after complete resection of noninvasive IPMNs is not negligible. Therefore, a long-term/life-time follow-up monitoring is of paramount importance to detect eventual recurrences.